2019
DOI: 10.1007/s00338-019-01838-0
|View full text |Cite
|
Sign up to set email alerts
|

El Niño-associated catastrophic coral mortality at Jarvis Island, central Equatorial Pacific

Abstract: The 2014-2017 Global Coral Bleaching Event is the longest, most widespread, and impactful on record. Rapid ecological assessment surveys by NOAA's Pacific Reef Assessment and Monitoring Program reported widespread coral mortality at Jarvis Island in the aftermath of the 2015-2016 super-El Nin ˜o warming event; hard coral cover declined from 18.7% in April 2015 (pre-bleaching) to 0.4% in May 2016 (post-bleaching), representing a catastrophic [ 98% decline. Between 2015 and 2016, corals at Jarvis experienced max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 43 publications
5
33
0
Order By: Relevance
“…While the full extent and impacts of the 2014-2017 GCBE are still emerging, this was the longest-lasting, most widespread, and most likely the most damaging on record. Heat stress values in some locations, including the central tropical Pacific, were the highest ever recorded as heat stress lasting for months, with continuous heat stress lasting up to a full year and resulting in almost complete coral loss (Eakin et al 2017;Brainard et al 2018;Vargas-Á ngel et al 2019). Even some of the hottest coral reef areas in the world succumbed to heat stress during the 2014-2017 GCBE, showing that heat stress had even exceeded their limits (Burt et al 2019).…”
Section: What Was Different In 2014-2017?mentioning
confidence: 99%
“…While the full extent and impacts of the 2014-2017 GCBE are still emerging, this was the longest-lasting, most widespread, and most likely the most damaging on record. Heat stress values in some locations, including the central tropical Pacific, were the highest ever recorded as heat stress lasting for months, with continuous heat stress lasting up to a full year and resulting in almost complete coral loss (Eakin et al 2017;Brainard et al 2018;Vargas-Á ngel et al 2019). Even some of the hottest coral reef areas in the world succumbed to heat stress during the 2014-2017 GCBE, showing that heat stress had even exceeded their limits (Burt et al 2019).…”
Section: What Was Different In 2014-2017?mentioning
confidence: 99%
“…In addition, between 2014 and 2017, "back-to-back" thermal anomalies occurred on the northeastern coast of Australia, causing massive coral bleaching in the north and mid sections of the Great Barrier Reef; this is arguably the worst-ever bleaching in the history of the GBR [7,8] and other parts of Australia [9,10]. Similar global-scale coral bleaching events (GCBE) that result in high coral mortality, the rapid decline of reef structures, and unprecedented environmental impacts have also been reported in the Indian [11,12], Pacific [13][14][15], and Atlantic Oceans [16,17]. Scientists have therefore concluded that the 2014-2017 GCBE represents the first multi-year, global-scale coral bleaching event to cause bleaching and mortality two or more times over the 3-year event [18].…”
Section: Coral Reef Ecosystems and The Impacts Of Environmental Changementioning
confidence: 89%
“…Nevertheless, well-protected reefs within MPAs are not shielded from thermal stress [150,151]. After the last bleaching event, this was confirmed for MPAs [152], and for remote and isolated reefs with almost no direct human pressures [23,24,27,[153][154][155].…”
Section: Perspectives For the Futurementioning
confidence: 86%
“…These global bleaching events are becoming more frequent (1998, 2010 and 2014-17) and severe [14,16,[18][19][20][21][22], leaving coral reefs vulnerable and unable to recover. The 2014-2017 mass bleaching event, which lasted 36 months and spanned four calendar years, was the longest-lasting, most widespread, and probably most damaging event on record [21][22][23][24][25][26][27][28][29], and stands out as unique by spanning all phases of the El Niño-Southern Oscillation cycle of 2017, being the warmest non-El Niño year ever recorded [21,30].…”
Section: Introductionmentioning
confidence: 99%